“A distortive glass of our distorted glebe”: mistranslation in Nabokov’s Ada - Taylor, Juliette (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article examines the theme of mistranslation in Nabokov ’s Ada or Ardor: A Family Chronicle in the context of the novel’s multilingual style. Focusing on a selection of deliberate mistranslations carried out by the cen-tral protagonists, Van and Ada Veen, the article demonstrates that such playful mistranslation serves a function that is much more significant than mere parody. Though, on the surface, the mistranslations parody those forms of ‘paraphrastic’ or ‘free’ translation that Nabokov and his cha racters consistently critique throughout Ada, each instance of deliberately ‘bad’ translation also contains extremely inventive forms of interlingual mutation and play which have aesthetically-productive defamiliarising effects. The article relates those instances of explicit mistranslation to the overall style of the novel, arguing that problems of interlingual transfer and communication are intrinsic to the multilingual aesthetic of the novel as a whole.